2023
DOI: 10.1136/jitc-2022-006311
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 gene amplification and focality: relationship with protein expression

Abstract: PD-L1 (CD274) amplification occurs in a small subset of malignancies and may predict anti-PD-1/PD-L1 immunotherapy responsiveness. We hypothesized that both copy number (CN) and focality of cancer-related PD-L1 amplifications impact protein expression, and, thus, analyzed solid tumors that underwent comprehensive genomic profiling between March 2016 and February 2022 at Foundation Medicine. PD-L1 CN alterations were detected using a comparative genomic hybridization-like method. PD-L1 CN changes were correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…5 One possible explanation is the fact that PD-L1 expression in NSCLC is not static but seems to undergo dynamic changes. [5][6][7][8][9] Previous studies found that PD-L1 expression may be influenced by several factors including Interferon-γ and other cytokines release, [10][11][12] activation of oncogenic drivers 6 13 and specific drugs. 14 Some studies even showed that oncological treatment may alter PD-L1 expression.…”
Section: Open Accessmentioning
confidence: 99%
“…5 One possible explanation is the fact that PD-L1 expression in NSCLC is not static but seems to undergo dynamic changes. [5][6][7][8][9] Previous studies found that PD-L1 expression may be influenced by several factors including Interferon-γ and other cytokines release, [10][11][12] activation of oncogenic drivers 6 13 and specific drugs. 14 Some studies even showed that oncological treatment may alter PD-L1 expression.…”
Section: Open Accessmentioning
confidence: 99%
“…However, immunotherapy biomarkers can perform differently under different circumstances. Although the 22C3 test of PD-L1 expression has been included in the National Comprehensive Cancer Network (NCCN) guidelines, some PD-L1-negative patients still respond to PD-1/PD-L1 inhibitors [ 104 , 105 ]. Moreover, the molecular subtypes of TNBC are under debate, indicating the heterogeneity of TNBC [ 106 ].…”
Section: Challenges In Tnbc Immunotherapymentioning
confidence: 99%